Analisis Kualitas Pelayanan terhadap Tingkat Kepuasan Pelanggan - Triana, Ika; Subakti, Agung Gita (THE Journal : Tourism and Hospitality Essentials Journal, 2017)
The purpose of this study is to analyze the service quality toward customer satisfaction at X Japanese Restaurant. The writer is using the descriptive and associative-causal method. 100 people who are visitors to the restaurant were taken as the sample for this research. The analysis that was used are t-test and by verifying the hypothesis, these methods were used to determine the final result or conclusion of the study. This study showed that customer satisfaction is 75,1 % influenced by service quality and it also reveals a very strong relation between service quality and customer satisfaction at X Japanese Restaurant.